Stretchable and wearable colorimetric patches based on thermoresponsive plasmonic microgels embedded in a hydrogel film. (September 2018) - Choe, Ayoung; Yeom, Jeonghee; Shanker, Ravi; Kim, Minsoo; Kang, Saewon; Ko, Hyunhyub
Abstract Stimuli-responsive colorimetric sensors are promising for various industrial and medical applications due to the capability of simple, fast, and inexpensive visualization of external stimuli. Here we demonstrate a thermoresponsive, smart colorimetric patch based on a thermoresponsive plasmonic microgel embedded in a stretchable hydrogel film. To achieve a fast and efficient thermoresponsive color change, raspberry-shaped plasmonic microgels were fabricated by decorating gold nanoparticles (AuNPs) on poly(N-isopropylacrylamide) (PNIPAM) microgels, which exhibit reversible and strain-insensitive color shifts (between red and grayish violet) in response to a temperature change. The smart colorimetric patch containing a plasmonic microgels exhibits a significant extinction peak shift (176 nm) in a short time (1 s), with a temperature-sensing resolution of 0.2 °C. Moreover, the transition temperature of the plasmonic microgel can be finely tuned by additives and comonomers, so that the exquisite temperature visualization can be conducted over a wide temperature range of 25‒40 °C by assembling plasmonic microgel films with different transition temperatures into an array patch. For proof-of-concept demonstrations, a freestanding smart colorimetric patch was utilized as a spatial temperature scanner and a colorimetric thermometer for a thermoresponsive actuator, which is potentially applicable in smart, wearable sensors and soft robotics. Wearable sensors: color-changing nanoparticles keep tabs on temperature Thin flexible patches that adhere to human skin and report deviations in temperature have been developed by researchers in South Korea. Hyunhyub Ko and colleagues from the Ulsan National Institute of Science and Technology made water-filled polymers known as hydrogels into microscale beads and coated them with light-emitting gold nanoparticles. They then embedded the beads into a stretchable transparent film. Because the tiny microgels swell and shrink in response to temperature, the nanoparticles likewise move closer or further apart, an action that causes them to produce differently colored light. The film, even when stretched or bent, detected temperature changes from 25 to 45 °C by vivid color changes. A prototype "smart hand" capable of rapidly sensing heat or cold when wrapped around fingertips or wrists could find use in soft robotics. A thermoresponsive smart colorimetric patch was fabricated by embedding thermoresponsive plasmonic microgels in a stretchable hydrogel film. The stretchable and wearable colorimetric patches exhibited vivid color change, fast response time, outstanding thermal resolution, and high durability. Potential applications in wearable smart sensors and soft robotics were demonstrated through a spatial temperature scanner and a colorimetric thermometer for thermoresponsive actuators.